GAZING AT ‘THE-YOU-KNOW-WHO/WHAT’ IN WHATSAPP: DEIXIS USED IN ONLINE LEARNING AMID COVID-19 PANDEMIC - Sugianto, Ahmad; Muslim, Ahmad Bukhori (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
WhatsApp, as one of the most powerful and ubiquitous social media platforms, has become one of the promising tools utilized for English online learning during the current crisis, COVID-19 pandemic. Nevertheless, interacting effectively via this platform might be challenging for messages communicated to this platform might have more than one meaning that is likely to result in misunderstanding among the users. Thus, understanding deixis, known as one of the interactional phenomena in which language and context can be figured out, is invaluable. Nevertheless, to the best of the writers’ knowledge, studies concerning the use of deixis with respect to WhatsApp for English online learning are still left under-researched. Therefore, the present study aimed to investigate the deixis employed during online learning via a WhatsApp group. The method utilized in this research was a descriptive study. Besides, the participants comprised 23 postgraduate students and an instructor from an English Education Study Program of one university in Bandung city. The data were taken from the artefact in the form of an online chat archive. Based on the data analyzed, the findings revealed that all the types of deixis encompassing personal, social, discourse, place, and time deixis were found in online learning through the WhatsApp application. In this regard, the person(al) deixis (46%) was the most frequently used deixis, followed by social (39%), discourse (8%), place (5%), and time deixis (2%), respectively. Moreover, the appropriate and effective use of deixis by the instructor was found to influence students’ engagement and critical thinking ability. Besides, the WhatsApp feature, emojis, was found to be utilized along with the deixis, as well as it assists in providing some emphasis, understanding of the messages conveyed, and showing respect or compliment among the participants.